2012
DOI: 10.1111/j.1349-7006.2011.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐ion radiation enhances migration ability and invasiveness of the pancreatic cancer cell, PANC‐1, in vitro

Abstract: Pancreatic cancer is an aggressive disease that responds poorly to conventional photon radiotherapy. Carbon‐ion (C‐ion) radiation has advantages compared with conventional radiotherapy, because it enables more accurate dose distribution and more efficient tumor cell killing. To elucidate the effects of local radiotherapy on the characteristics of metastatic tumors, it is necessary to understand the nature of motility in irradiated tumor cells; this will, in turn, facilitate the development of effective strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 37 publications
1
62
0
Order By: Relevance
“…their migration and invasion (4). Here, we found that C-ion irradiation at 0.5, 1, 2, and 4 Gy dose-dependently inhibited the migration and invasion of MIAPaCa-2 cells (Fig.…”
Section: C-ion Radiation Suppresses Miapaca-2 Cell Migration and Invamentioning
confidence: 59%
See 4 more Smart Citations
“…their migration and invasion (4). Here, we found that C-ion irradiation at 0.5, 1, 2, and 4 Gy dose-dependently inhibited the migration and invasion of MIAPaCa-2 cells (Fig.…”
Section: C-ion Radiation Suppresses Miapaca-2 Cell Migration and Invamentioning
confidence: 59%
“…Furthermore, we found that in AsPC-1 and BxPC-3 cells, C-ion irradiation also significantly decreased the levels of GTP-bound Rac1 without affecting total Rac1 expression (Fig. 4C, D), which correlated with the inhibition of cell migration (4). The decrease in GTP-bound Rac1 was rescued by the treatment with epoxomicin (Fig.…”
Section: C-ion Radiation Inhibits Rac1 and Rhoa Activities Via Proteamentioning
confidence: 65%
See 3 more Smart Citations